2022
DOI: 10.1101/2022.04.30.486882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The highly conserved stem-loop II motif is important for the lifecycle of astroviruses but dispensable for SARS-CoV-2

Abstract: The stem-loop II motif (s2m) is an RNA element present in viruses from divergent viral families, including astroviruses and coronaviruses, but its functional significance is unknown. We created deletions or substitutions of the s2m in astrovirus VA1 (VA1), classic human astrovirus 1 (HAstV1) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). For VA1, recombinant virus could not be rescued upon partial deletion of the s2m or substitutions of G-C base pairs. Compensatory substitutions that restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 51 publications
(226 reference statements)
0
8
1
Order By: Relevance
“…6 ). Despite the observations that modifications to the s2m sequence in the genome of the human astrovirus resulted in reduced replication in vitro ( 44 ), our findings that modifications to the IBV s2m sequence did not affect replication are not entirely unexpected, as not all coronaviruses contain an s2m-associated sequence or -associated RNA structure ( 24 ). A previous study investigating sequences deposited in GenBank did not identify an s2m-associated sequence in any of the available sequences corresponding to alphacoronaviruses ( 24 ) or the betacoronaviruses, apart from SARS-CoV.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…6 ). Despite the observations that modifications to the s2m sequence in the genome of the human astrovirus resulted in reduced replication in vitro ( 44 ), our findings that modifications to the IBV s2m sequence did not affect replication are not entirely unexpected, as not all coronaviruses contain an s2m-associated sequence or -associated RNA structure ( 24 ). A previous study investigating sequences deposited in GenBank did not identify an s2m-associated sequence in any of the available sequences corresponding to alphacoronaviruses ( 24 ) or the betacoronaviruses, apart from SARS-CoV.…”
Section: Discussioncontrasting
confidence: 86%
“…The s2m sequence in human astrovirus 1 (HAstV1) spans the capsid-coding region and 3′ UTR, so the s2m-deficient virus, (HAstV1-s2m Δ25–43 , Fig. 8A ) was designed and rescued with 19 nt of the noncoding half of s2m deleted ( 44 ). Unlike the generated rIBVs with s2m modifications, HAstV1-s2m Δ25–43 exhibited a <log reduction in replication in vitro ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S2m of SARS-CoV-2 was recently reported to interact with the human cellular miRNA-1307-3p, which is predicted to regulate the translation of some interleukins (among which IL18), interleukin receptors, and the interferon alpha receptor, being putatively able to manipulate the host immune response ( Imperatore et al, 2022 ). It was also reported that antisense oligonucleotides may interact with this s2m element, inhibit SARS-CoV-2 replication in culture ( Lulla et al, 2021 ), decrease astrovirus titers and reduce the activity of an astrovirus replicon ( Lulla et al, 2021 ; Janowski et al, 2022 ). However, Janowsky et al did not observe that deletion or mutation of s2m of SARS-CoV-2 altered viral growth in vitro ( Janowski et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that antisense oligonucleotides may interact with this s2m element, inhibit SARS-CoV-2 replication in culture ( Lulla et al, 2021 ), decrease astrovirus titers and reduce the activity of an astrovirus replicon ( Lulla et al, 2021 ; Janowski et al, 2022 ). However, Janowsky et al did not observe that deletion or mutation of s2m of SARS-CoV-2 altered viral growth in vitro ( Janowski et al, 2022 ). It was also hypothesized that s2m could intervene in the protection of the viral genome from degradation by host ribonucleases ( Tengs and Jonassen, 2016 ).…”
Section: Discussionmentioning
confidence: 99%